UTILIZATION OF RADIO TELESCOPES IN DETERMINING THE BEGINNING OF THE ISLAMIC CALENDAR - Anaam, Khairul (Al-Hilal: Journal of Islamic Astronomy, 2024)
This study analyzes the use of radio telescopes in rukyat al-hilāl observations from the perspective of science and fiqh. In modern astronomy, radio telescopes have become essential for observing celestial objects emitting radio signals, including planets, stars, and other cosmic phenomena. However, its use in observing the Hilāl as a marker of the beginning of the Islamic month is still debated, especially from the perspective of Islamic law (fiqh). This study uses a literature study method with a qualitative descriptive approach. The study's results indicate that this technology is not scientifically suitable for detecting the hilāl and determining the beginning of the Hijri month. Meanwhile, from a fiqh perspective, radio telescopes cannot be considered valid for observing the hilāl in determining the beginning of the Hijri month. Observing the hilāl in determining the beginning of the Hijri month requires a visual vision of the crescent moon object visible after sunset as a sign of the start of the new month in the Hijri calendar.